Area in the West End, July 17, 1958 - York, Raymond (Tufts Archival Research Center, 2005)
Street-level view of an area in the West End. Buildings and street lights line both sides of the street, and automobiles are included in the photograph. 3 15/16 x 2 5/8, 4 1/2 x 3 1/4 overall Photographs